The Role of NcRNAs to Regulate Immune Checkpoints in Cancer - Jiang, Yicun; Zhao, Leilei; Wu, Yiwen; Deng, Sijun; Cao, Pu; Lei, Xiaoyong; Yang, Xiaoyan (Frontiers in Immunology, 2022)
Nowadays, the incidence of cancer is becoming more and more common, and the treatment of cancer has always been a problem, although a small number of cancers can be treated, but the recurrence rates are generally high and cannot be completely cured. At present, conventional cancer therapies mainly includes chemotherapy and radiotherapy, they are the first-line therapies of most cancer patients, but there are palliatives. Treatments are not updated as fast as cancer. Current cancer treatments have not been effective in stopping the development of cancer, cancer treatment needs to be imported into new strategies. Noncoding RNAs (ncRNAs) research is a hot topic at present. NcRNAs participate in all aspects of cancer biology, and they include MicroRNAs (mir-RNAs), circular RNAs (circ-RNAs) and long-coding (lnc-RNAs) RNAs. All above ncRNAs are involved in the progress of tumors in a new form, that is the targeted effect on immune checkpoints. NcRNAs target various immune checkpoints to affect tumor proliferation differentiation and development process. This would be a new strategy for cancer treatment.